If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9w-11=7(w+3)
We move all terms to the left:
-9w-11-(7(w+3))=0
We calculate terms in parentheses: -(7(w+3)), so:We get rid of parentheses
7(w+3)
We multiply parentheses
7w+21
Back to the equation:
-(7w+21)
-9w-7w-21-11=0
We add all the numbers together, and all the variables
-16w-32=0
We move all terms containing w to the left, all other terms to the right
-16w=32
w=32/-16
w=-2
| 56-2s=40 | | 5=-3x+3x | | x-2/10=2x/25 | | -1+7y=-4y+10y+4 | | 8(1-x)=-7x+16 | | 6/m=3/7 | | -16x-4=55 | | x^2-444x=-6000 | | 3y-11=2y+5 | | -30-5y+8y=-24 | | -3h-8+5h=2(h-4) | | 8r-2=-4r-7r-2 | | x+12=−14 | | 36000+1500x=29000+2500x | | 7m+3-8m=-5 | | 7t+2t-3=-3(1-3t) | | 6x+9+4x=14 | | 7-3r=r-4(2-r)+9 | | -2x-3=4x+21 | | 3x4x=25 | | 175m-125m+48500=50250-200m | | 3x+(12x+1)+(16x-7)=180 | | 9x-“=9 | | x-130=-8x+104 | | 20m+2=100 | | 19+4.50h=10+5.75h | | 6-3(3x-40)=-27 | | n-6=2n-8 | | 6(x+1)=3x-12 | | -4j+18=-8-12j+18 | | -147=6(8n-3)-5n | | 2(x+4)-3=3(x+1)-x+2 |